Rīgas tēls mūsdienu latviešu un krievu dzejā. - Laizāne, Kristīne (Latvijas Universitāte, 2023)
Bakalaura darba mērķis ir aplūkot un analizēt Rīgas tēlu mūsdienu dzejā. Autors veic dažādu autoru dzejoļu analīzi, izmantojot un izceļot tieši dzejoļos ietvertos simbolus. Īpaša nozīme tika pievērsta tam, lai dzejoļi pārstāvētu gan latviešu, gan Latvijas krievu dzejnieku daiļradi.

The aim of the bachelor's paper is to define and analyze the image of Riga in modern poetry. The author performs an analysis of poems about Riga, which are written by different authors. The main task is to highlight the symbols, which directly resonates with the image of the city. It was particularly important that the poems represent both Latvian and Latvian Russian poets.
The Image of Riga in Contemporary Latvian and Russian Poetry.
Keywords: Valodniecība; Рига; образ; современная поэзия; анализ